Test-retest reliability, agreement and construct validity of the International Physical Activity Questionnaire short-form (IPAQ-sf) in people with COPD. (January 2023) - Flora, Sofia; Marques, Alda; Hipólito, Nádia; Morais, Nuno; Silva, Cândida G.; Januário, Filipa; Rodrigues, Fátima; Carreira, Bruno P.; Cruz, J.
Abstract: Introduction: This study assessed the test-retest reliability/agreement and construct validity of the International Physical Activity Questionnaire short-form (IPAQ-sf) in patients with chronic obstructive pulmonary disease (COPD). It also explored differences in its validity according to age, sex and GOLD airflow obstruction levels. Methods: 62 participants (68 ± 8 years, 53 males, FEV1 51 ± 23%pred) completed the Portuguese IPAQ-sf, wore an accelerometer for 7 days and completed a second IPAQ-sf. Test-retest reliability/agreement was assessed with Intraclass Correlation Coefficient (ICC2, 1 ), 95% Limits of Agreement (LoA), standard error of measurement (SEM) and minimal detectable change (MDC95 ) for continuous variables, and percentage of agreement (%agreement) for categories ("active"/"inactive"). Validity was assessed with 95% LoA and Spearman's correlations (ρ) between IPAQ-sf 2 (METs-min/week, time in vigorous [VPA], moderate PA [MPA] and walking) and accelerometry (time in MVPA, VPA, MPA and step counts) for continuous variables; %agreement, Cohen's kappa, and sensitivity specificity and±predictive values for categories. Correlations were also performed for age, sex and GOLD airflow obstruction grades. Results: Reliability was good (ICC2, 1  = 0.707) with wide LoA (-6446—6409 METs-min/week). SEM and MDC95 were 1840 and 4971 METs-min/week, respectively. %agreement between the two IPAQ-sf was 84% (kappa = 0.660). Positive, moderate and significant correlations were found between IPAQ-sf and accelerometry (0.396 ≤ ρ ≤ 0.527, p < 0.001), except for VPA (p > 0.05). The strongest correlations were found in age (<65 years) and male (0.466 ≤ ρ ≤ 0.653, p < 0.05). %agreement between tools was 65% (kappa = 0.313), with high sensitivity (0.830) but low specificity (0.500). Conclusions: The IPAQ-sf seems valid to be used in COPD but caution on its widespread use is recommended as its accuracy may be limited. Highlights: The IPAQ-sf presented good test-retest reliability results but wide limits of agreement. The wide LoA suggest that it may not be appropriate to assess patients' PA levels throughout time. Overall, the IPAQ-sf showed positive and moderate correlations with accelerometry. The IPAQ-sf seems to be valid in COPD but caution on its widespread use is recommended as its specificity is low.